Aesthethic and masticatory rehabilitation on post mandibular resection with combination of hollow obturator and hybrid prosthesis - Arif Rachman; Eha Djulaeha; Utari Kresnoadi (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Replacing tooth lost caused by caries, periodontal disease, trauma and neoplasm including ameloblastoma which requires mandibular resection is important. Purpose: The aim of the study to rehabilitation of post mandibular resection with combination of hollow obturator and hybrid prosthesis. Case: A patient 25 years old, male, for having prosthesis to cover defect due to post right mandibular resection. Case Management: In this presented case, mandibular plate was applied due to spreading defect with losing almost a half body of mandible (class II modification 2 according to cantor and curtis classification). The design of therapy was mandibular obturator using hybrid prosthesis (removable partial denture metal frame and fixed splint crown with precision attachment) with hollow obturator. The application was based on several advantages: good aesthetic performance, retention, stability, lighter weight and equal share of vertical load for teeth on non surgical site. The result of control I, II, III, showed that aesthetic performance, masticatory function, speech and swallowing were in good condition. Conclusion: The design of mandibular obturator using hybrid denture with hollow obturator could rehabilitate aesthetic performance, masticatory function, speech and swallowing for patient with post mandibular resection.